(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
This paper presents a core concept of transaction. Basically transaction is a unit of interrelated operations to perform a unit of task. ACID property must be preserved during whole transaction where ‘A’ stands for atomicity, ‘C’ stands for consistency, ‘I’ stands for isolation and ‘D’ stands for durability. Durability is maintained by setting RAID (redundant array independent disk) architecture. Serial schedules are very good in terms of maintaining ACID property because risk in these type of schedules is very low but the throughput and degree of concurrency in serial scheduling is very low.